Sanksi Pidana Terhadap Pengemudi Kendaraan Bermotor Tanpa Dilengkapi Surat Tanda Nomor Kendaraan di Wilayah Hukum Kabupaten Tanjung Jabung Barat - R.M Ferry Irawan; Bunyamin Alamsyah; Nyimas Enny Fitriya Wardhany; Iman Hidayat (Legalitas: Jurnal Hukum, 2026)
Motor vehicle drivers without a Vehicle Registration Certificate (STNK) in the Tanjung Jabung Barat Regency area have increased over the past 3 years, which prompted interest in conducting research in the form of a thesis aimed at understanding and analyzing criminal sanction enforcement, obstacles, and efforts against motor vehicle drivers without a Vehicle Registration Certificate in the Tanjung Jabung Barat Regency area. The research method used is Empirical Normative Juridical. The enforcement of criminal sanctions against motor vehicle drivers without a Vehicle Registration Certificate in the Tanjung Jabung Barat Regency area begins with the seizure of those who cannot show the Original STNK, with the vehicle being immediately towed and stored at the Satlantas Polres Tanjung Jabung Timur, accompanied by a seizure report (BAP). For drivers who can show the original vehicle registration certificate (STNK) or a photo of the original STNK, they are still given traffic fines after verification. The challenges faced by the Tanjung Jabung Barat Police in enforcing criminal sanctions against motor vehicle drivers without a Vehicle Registration Certificate in the Tanjung Jabung Barat area include: the driver themselves, the law enforcers, in this case, the lack of supervision from relevant parties or coordination, such as the SAMSAT of Tanjung Jabung Barat, limited vehicle storage space at the Traffic Unit of Tanjung Jabung Barat Police, insufficient socialization and legal counseling to the public, lack of legal awareness and ethics, and some people still thinking that criminal sanctions have no deterrent effect because they can be paid via e-ticketing with a maximum amount of Rp. 500,000 (five hundred thousand rupiah). Efforts carried out by the Tanjung Jabung Barat Police in enforcing criminal sanctions against motor vehicle drivers without Vehicle Registration Certificates in the Tanjung Jabung Barat Regency legal area include adding personnel to the Tanjung Jabung Barat Traffic Unit, increasing police discretion to reduce congestion at the traffic unit, enhancing cooperation with the Tanjung Jabung Barat SAMSAT to speed up vehicle tax payments and STNK validation, socializing and providing legal counseling about the importance of STNK and the criminal sanctions regulated in the Road Traffic Law. It requires the role and cooperation of the community to comply with and adhere to the mandatory rules for having an STNK in addition to a driving license, helmet, and other rider safety measures. The suggestions put forward include the need to increase the number of personnel and infrastructure in the Traffic Unit of Tanjung Jabung Barat Police, the need for synergy between Tanjung Jabung Barat Police and SAMSAT Tanjung Jabung Barat regarding the importance of vehicle registration (STNK) and speeding up the bureaucracy for tax payments and registration verification, and increasing socialization and legal counseling to the public that driving without a valid STNK is a traffic violation and carries criminal sanctions as regulated in the traffic and road transport law.